PO05 | Intensive FVIII replacement in haemophilia patients with hypertrophic synovium: a randomized study (Bleeding, Thrombosis and Vascular Biology, 2025)
Background and Aims: Hypertrophic synovium (HS) is a marker of disease activity in patients with haemophilia (PwH). Although some recommendations suggest intensifying prophylaxis in PwH with HS, no validated schedules are available. We explored the efficacy of intensive Factor VIII (FVIII) replacement treatment in PwH with HS.